Examine the Empirical Relationship between Energy Consumption and Industrialization in Bangladesh: Granger Causality Analysis - Rahman, Md. Hasanur; Ruma, Alfarunnahar; Hossain, Mohammad Nasir; Nahrin, Rifat; Majumder, Shapan Chandra (International Journal of Energy Economics and Policy, 2021)
The current study examines the empirical relation between energy consumption and industrialization concerning other macroeconomic variables like as infrastructure, manufacturing, and capital formation with covering the period from 1975 to 2018. The Johansen co-integration estimation asserts the long-run association in this process. Whatever granger causality shows the bidirectional causality between electricity consumption and industrialization. Capital formation and industrialization have the bidirectional causality also. A unidirectional causality exists between oil and industrialization where manufacturing and industrialization have bidirectional causality. The estimated result of the error correction mechanism (ECM) shows the speed of long-run equilibrium at 45% within the time. The ECT has been significant at a 1% level with a pessimistic sign. The assistances of this attempt ensuring the importance of energy use and energy supervision in the aspect of industrial enlargement with making an allowance for the other macroeconomic indicators. Keywords: Industrialization, Energy, DOLS, Granger Causality JEL Classifications: O13, 014, P18, Q43 DOI: https://doi.org/10.32479/ijeep.10843